2007
DOI: 10.1007/s11162-007-9066-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Up: Examining the Connections among State Structural Characteristics, Regulatory Practices, and Performance

Abstract: Using Measuring Up data from 2000, 2002, 2004, and 2006, this study examines the extent to which the state performance grades, and changes in grades, are associated with the characteristics of each state and its arrangements for higher education governance and control. To what extent is each state's higher education performance a product of relatively controllable governance and regulatory practices versus relatively uncontrollable measures of state size, affluence, and demographics? Using both Time Series Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 17 publications
4
51
0
Order By: Relevance
“…Unfortunately, much of the research that examines the impacts of these policies, particularly in the area of higher education, skips the intermediate links in the causal chain and focuses exclusively on whether the adoption of performance policies result in improved student success. As a result, we have some limited information about whether accountability policies were successful in bringing about improved performance (Volkwein and Tandberg 2008), but we have very limited systematic analysis that can tell us why (or why not). If accountability policies are ineffective at affecting institutional performance with respect to student outcomes, as some previous research has suggested (Volkwein and Tandberg 2008), is this failure due to poor implementation, or is it because the changes in organizational behavior that they seek to promote are not, in fact, effective ways to improve the kinds of outcomes that they are concerned about?…”
Section: Performance Funding In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, much of the research that examines the impacts of these policies, particularly in the area of higher education, skips the intermediate links in the causal chain and focuses exclusively on whether the adoption of performance policies result in improved student success. As a result, we have some limited information about whether accountability policies were successful in bringing about improved performance (Volkwein and Tandberg 2008), but we have very limited systematic analysis that can tell us why (or why not). If accountability policies are ineffective at affecting institutional performance with respect to student outcomes, as some previous research has suggested (Volkwein and Tandberg 2008), is this failure due to poor implementation, or is it because the changes in organizational behavior that they seek to promote are not, in fact, effective ways to improve the kinds of outcomes that they are concerned about?…”
Section: Performance Funding In Higher Educationmentioning
confidence: 99%
“…In recent years, there have been several initiatives, at both the state and federal levels, to directly link performance to funding (Aldeman and Carey 2009a;Burke 2002;Zumeta 2001). While there have been a few attempts to uncover the impacts associated with these higher education performance funding policies (Volkwein and Tandberg 2008), our knowledge about them has thus far largely been based on anecdotal evidence and limited case studies (Banta, Rudolph, Dyke, and Fisher 1996;Doyle and Noland 2006;Sanford and Hunter 2010). As such, there remain serious gaps in our empirical knowledge about the extent to which these policies are having substantive impacts on budgetary processes at the state level and on service delivery at the organizational level.…”
Section: Introductionmentioning
confidence: 99%
“…Notoriously, in 2008, 49 states received "failing" grades on affordability (the cost of attending college relative to median family income), and all states received an "incomplete" on student learning due to insufficient data to allow for cross-state comparisons (Lederman, 2010). These outcomes, however, seem more associated with factors over which states have little direct control, such as wealth, education levels, and growth, than with factors they can substantively influence, such as higher education governance structures and accountability systems (Volkwein & Tandberg, 2008).…”
Section: Privatization and Accountability Trends In The Usmentioning
confidence: 98%
“…Contextual factors such as prevailing wages, unemployment rates, and demand for specialized degrees have been shown to impact institutional performance and the benefits derived from college completion (Volkwein & Tandberg, 2008). Because many graduates turn first to their local labor market for employment (Perry, 2001), we expect between-state variation in labor market conditions to affect ROI, net of student and institutional factors.…”
Section: Contextual Factorsmentioning
confidence: 99%